Assessing Drug Consumption Behavior With the Heidelberger Drogenbogen (Heidelberg Drug Scales): Reliabilities, Validities, and Cut-Off Criteria. (10th November 2015) - Aguilar-Raab, Corina; Heene, Moritz; Grevenstein, Dennis; Weinhold, Jan
Abstract : Background: The Heidelberger Drogenbogen (HDB) is a German language assessment of substance-specific knowledge and consumption patterns of the illicit psychoactive substances cannabis, MDMA (ecstasy), amphetamines, cocaine, and hallucinogens. The behavior modules for each of these five drugs/drug groups allow for a diagnostic evaluation of the extent of harmful consumption behavior. Each of the five modules represents a single standardized test. Objectives: This paper outlines several statistical parameters, Cronbach's alpha, retest reliabilities, as well as numerous validity and cut-off-criteria of the behavioral modules. Methods: Participants ( N = 4, 794) were recruited at schools, universities, in subcultural contexts, and in institutions of substance abuse treatment. Results: Internal consistencies range from = .68 to .79 while test–retest reliabilities between .87 and .94 were found. The behavior modules of the HDB can discriminate between populations with and without clinical levels of substance use. Furthermore, this measure has incremental validity and higher diagnostic accuracy over competing measures. Conclusions: The behavior modules of the HDB are reliable and valid measures of substance use and misuse.